Effects of explant type, plant growth regulator and cultivation system on multiplication of Polygonum multiflora Thunb. cultured in vitro - Luan, Vu Quoc; Thi Luyen, Do; Hoang Anh Kha, Ho; Thanh Tung, Hoang; Thi Hien, Vu; Manh Cuong, Do; Van The Vinh, Bui; Gia Bao, Huynh; Tan Nhut, Duong (Vietnam Journal of Biotechnology, 2020)
Polygonum multiflora Thunb. (Belongs to Polygonaceae family) is a medicinal plant of economic value and should be protected, according to the Red Book of Vietnam. Many studies have shown that P. multiflora Thunb. was effective for many diseases such as hair loss, premature gray hair, lower back pain, knee weakness, muscle weakness, hemiplegia, nervousness, dizziness, insomnia, etc. Propagation and preservation of this herbal species are significantly important because of increased demand. Adventitious root biomass culture has been successful on a number of plant species, and that it has potential for P. multiflorum breeding. In this study, the effect of explants, plant growth regulators and different culture systems on adventitious root formation was investigated. The adventitious roots were induced from the explants and the optimum culture medium were transferred to four different culture systems (3-liter triangular flask, shaking triangle, bioreactor self-made and Korean bioreactor) containing 5 g adventitious roots per 1 liter medium. The results showed that the leaf cultured on SH medium supplemented with 1.5 mg L-1 IBA, 30 g L-1 sucrose, 8.5 g L-1 agar and pH 5.8 gave the higher of adventitious root regeneration rate (100%), root number/explant (25.33 roots), fresh weight (131.67 mg) and dry weight 13.35 mg) compared to those cultured on other condition after 6 weeks of culture. The adventitious root multiplication in the Korea bioreactor system is more effective than other culture systems shown in the fresh biomass (17.04 g), dry biomass (1.56 g) and proliferation rate (3.40 fold) after 6 weeks of culture.